Impact of Corporate Governance on Corporate Sustainable Growth - Mukherjee, Tutun; Sen, Som Sankar (Universitas Prasetiya Mulya, 2019)
It is believed that good corporate governance practices assist significantly in uplifting corporate performance, and brings in business success and sustainability. This study aims to shed light on the impact of corporate governance practices on corporate sustainable growth in India. A sample size of leading 139 non-financial companies listed in NSE for five years has been used in this study. Using longitudinal data analysis, the findings of the study suggest that Board Size (BS) and the Board Independence (B-IND) exercise strong influence in explaining the Corporate Sustainable Growth in India after controlling the effect of Leverage (LEV).